Hydrophilic interaction chromatography-tandem mass spectrometry based on an amide column for the high-throughput quantification of metformin in rat plasma. Issue 123 (25th November 2015) - Shi, Rong; Xu, Xining; Wu, Jiasheng; Wang, Tianming; Li, Yuanyuan; Ma, Bingliang; Ma, Yueming
Abstract : A simple, highly sensitive, specific, reproducible, and high-throughput Amide-HILIC-MS/MS assay to quantify metformin in rat plasma was established and successfully applied for sample analysis to support pharmacokinetic studies. Abstract : Metformin, a biguanide derivative, is the most commonly prescribed medication in the treatment of type 2 diabetes mellitus, among other diseases. Because it is highly polar, determining the concentration of metformin using reversed-phase liquid chromatography is often very challenging. Here, we demonstrate the utility of a novel hydrophilic interaction liquid chromatography method that is based on an amide column with tandem mass spectrometry. Chromatographic separation was achieved using an ACQUITY UPLC bridged ethyl-siloxane/silica hybrid amide column (2.1 × 100 mm, 1.7 μm). The isocratic mobile phase consisted of water and acetonitrile (v/v, 1 : 9), which both contained 0.06% formic acid and 5 mM ammonium formate at a flow rate of 0.5 mL min −1 . Data from validation experiments demonstrated that this new method is highly selective, sensitive (2.0 pg on column), and free of matrix and residual effects. The method was also precise (relative standard deviation of < 10.1%), accurate (96.9–105.7%), and linear ( r ≥ 0.995) over the ranges of 2–1024 ng mL −1 for metformin. The developed method was successfully applied to determine the metformin level in the plasma of rats that received a single dose of metformin (100 mg kg −1 ). Thus, this new method can be used as a tool for the clinical monitoring of metformin and for evaluating drug–drug interactions.